2019
DOI: 10.1002/gj.3624
|View full text |Cite
|
Sign up to set email alerts
|

Source of aeolian dune sands on the northern margin of Qarhan Salt Lake, Qaidam Basin, NW China

Abstract: The aeolian landforms in the Qaidam Basin have drawn increasing attention from geomorphologists for their morphological and formation mechanisms' similarities with their counterparts on Mars and Titan. Using grain-size and mineral composition data, this study investigated the source of aeolian dune sands found on the northern margin of Qarhan Salt Lake in the south central part of the Qaidam Basin. Results indicate that linear dune sands and gobi surface sediments are mainly composed of fine and very fine sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Mineral composition investigation can give discernment to the provenance and evolution of aeolian sand dunes [31], [32]. The main mineral constituents of dune sands are quartz and feldspar, with the total content of these minerals can reach up to 90% in some deserts [33], [34].…”
Section: Mineral Composition Of the Sand Dunesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral composition investigation can give discernment to the provenance and evolution of aeolian sand dunes [31], [32]. The main mineral constituents of dune sands are quartz and feldspar, with the total content of these minerals can reach up to 90% in some deserts [33], [34].…”
Section: Mineral Composition Of the Sand Dunesmentioning
confidence: 99%
“…Mineral composition investigation can give discernment to the provenance and evolution of aeolian sand dunes [31], [32]. The main mineral constituents of dune sands are quartz and feldspar, with the total content of these minerals can reach up to 90% in some deserts [33], [34]. Sand dune deposits in the study area are a mixture of various minerals in different content such as carbonate (calcite and dolomite), gypsum, silicate minerals such as quartz feldspar, clay minerals with the following abundance sequence quartz > calcite > clay minerals < feldspar < dolomite < gypsum.…”
Section: Mineral Composition Of the Sand Dunesmentioning
confidence: 99%
“…Diverse methods have been adopted to investigate the origin of desert sediments, such as grain size analysis, geochemical tracing, detrital mineralogy, scanning electron microscopy (SEM), satellite imagery, environmental magnetism, detrital zircon, and numerical modeling (Honda et al, 2004;Howari et al, 2007;Pan et al, 2016). For example, the grain-size characteristics of dune sands contain a mass of information about the transport pathways and potential sources of the sediment (Li et al, 2019). Geochemical analysis, especially of trace and rare Earth elements (REE), has great potential in identifying the provenance and transport pathways of sediments since they are less fractionated during weathering, transport, and sedimentation (Dehghani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the geochemical element composition of dune sands in different grain-size fractions, Du et al (2018) found that coarse components (75-500 μm) were derived from local fluvial and alluvial-diluvial deposits, whereas fine components (<75 μm) were derived from the Tarim Basin. Based on the characteristics of geochemical elements and mineral assemblages in dune sands and surface sediments from potential source areas, Li et al (2018Li et al ( , 2020 found that both gobi surface sediments and yardang corridor sands could provide sandy material to support the development of linear dunes on the northern margin of the Qarhan Salt Lake, which is a residual of ancient lake. These sands were derived from granite and granodiorite rocks in the Qilian Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…The Qaidam Basin is a closed inland fault basin, and northerly and northwesterly winds are the dominant aeolian forces in the basin. Linear and barchan dunes in the Sebei area developed under a broad unimodal wind regime(Li et al, 2020), whereas barchan dunes in the piedmont of the Lvliang Mountains were mainly influenced by northwesterly winds (Fig.3a). These two dune types coexist in the western part of the Qarhan Salt…”
mentioning
confidence: 99%